Strategi Komunikasi dalam Upaya Penerapan Sustainable Tourism Development di Pulau Derawan - Arvina Sandra; Hairunnisa; Fareis Althalets (Jurnal Komunikasi Korporasi dan Media (JASIMA), 2020)
Sustainable tourism development is an innovation to face the post oil and gas and coal economic transformation in East Kalimantan. This study aims to determine and analyze the implementation of Sustainable Tourism Development in East Kalimantan, especially on Derawan Island, Berau Regency. This research uses an intrinsic case study which was conducted during the period August 2018 to September 2018. The results of this study indicate that ongoing evaluation and coordination are still needed in order to create an integrated government, especially between the East Kalimantan Provincial Tourism Office and the Berau Regency Culture and Tourism Office in implementing Sustainable Tourism. Development on Derawan Island, which is a National Tourism Strategic Area (KSPN). Integrated coordination between local governments, district governments, stakeholders and communities will facilitate communication channels to convey messages in order to achieve optimal goals. In addition, public awareness on Derawan Island facilitates incoming innovation, and can help implement tourism development in accordance with the principles of sustainability.